Pediatric acute liver failure in Brazil: Is living donor liver transplantation the best choice for treatment?. Issue 7 (July 2016) - Tannuri, Ana Cristina Aoun; Porta, Gilda; Kazue Miura, Irene; Santos, Maria Merces; Moreira, Daniel de Albuquerque Rangel; de Rezende, Nathassia Mancebo Avila; Miyatani, Helena Thie; Tannuri, Uenis
Abstract : Acute liver failure (ALF) in children is a life‐threatening condition that often leads to urgent liver transplantation (LT). The aim of the present investigation was to describe the experience in Brazil in treating pediatric ALF, with an emphasis on the role of living donor liver transplantation (LDLT) in treating this condition. All children with ALF who fulfilled the criteria for an urgent LT were admitted to the intensive care unit. Patients were divided into 2 groups based on the moment of admission: before and after June 2007, when the LDLT program for ALF was started. Statistical analyses were performed to identify prognostic factors of patients with ALF. For the study, 115 children with ALF were admitted. All patients had some degree of encephalopathy. Among the patients, 26% of them required intracranial pressure monitoring (IPM), 12.8% of the patients required hemodialysis, and 79 patients underwent transplantation (50 deceased donors and 29 living donors) corresponding to 12.4% of all pediatric LTs. Only 9 children recovered without LT. The need for IPM and nonperformance of LT were related to a higher mortality. The mortality rate of patients who underwent LT was significantly lower than that of children with ALF who did not undergo a LT (48.1% versus 75%; P = 0.02). The incidences of primary nonfunction and mortality were statistically higher among deceased donor liver transplantations than LDLTs. Finally, it was verified that the overall survival rate of transplanted patients was increased after the introduction of LDLT ( P = 0.02). In conclusion, ALF in children continues to be a severe and devastating condition, and a LT should be performed promptly. The introduction of LDLT could increase the survival rate of patients in Brazil. Liver Transplantation 22 1006–1013 2016 AASLD